Impact of acceptance and commitment-based therapy on emotional adjustment and cognitive flexibility - Parvane ghodsi, Hoorieh Gheysari, (Opción, 2019)
This study aimed at determining the impact of acceptance and commitment-based therapy (ACT) on emotional adjustment and cognitive flexibility in middle-aged depressed women. Quasi experiment method of pretest and posttest with control group was used in this research. Findings obtained from this research showed that ACT had impact on emotional adjustment and cognitive flexibility in middle-aged depressed women (P<0.05). In conclusion, acceptance in ACT does not mean accepting annoying emotions and experiences or bearing them or resisting against them, but it is defined as a tendency to experience unpleasant events.